The politics of legal expertise in EU policymaking - Leino-Sandberg, Päivi 1976- (Cambridge University Press, 2021)
Legal advisers working in the institutions of the European Union exercise significant power, but very little is known about their work. Notwithstanding the handful of cases where legal matters find their way into the news, legal advice remains invisible in EU policy making. For more than ten years Päivi Leino-Sandberg was a part of the invisible community of EU legal advisers, and participated in the exercise of their power. In this book, she shares her insights about how law and lawyers work in the EU institutions, and what their role and impact is on EU decisions from within the decision-making structure. She draws on interviews with over sixty EU lawyers and policymakers: legal experts who interpret the Treaties within the Institutions, draft legislation and defend the Institutions before the EU Court. Telling the true stories behind key negotiations, this book explores the interplay and tensions between legal requirements and political ambitions
Keywords: European Union / Officials and employees; Europäische Union; Government attorneys / European Union countries; Legislation / European Union countries; Politische Willensbildung; Juristische Argumentation; Politische Entscheidung